Pengaruh Laba Akuntansi, Arus Kas Operasi, Price To Book Value, Dan Kinerja Keuangan Perusahaan Dengan Pendekatan Economic Value Added Terhadap Return Saham (Studi Kasus Pada Saham Perusahaan Pertambangan Di Bursa Efek Indonesia Periode Tahun 2008-2010) - Ismail Marzuki; Susi Handayani (AKRUAL: JURNAL AKUNTANSI, 2012)
AbstractThe objectives of this research is to examine and analyze the influence of Accounting Profit, Operation Cash Flow, Price to Book Value, and Company Financial Performance Through Economic Value Added Approach to stock return of mining company that listed at Indonesia Stock Exchange in the period of 2008 2010. This research was an causal research with quantitative approach. The analyzing technique used in this research is multiple linier regressions analysis with SPSS program version 11.5. The result of this research shows that variable of accounting profit and operation cash flow do not have significant influence to stock return. While, variable of Price to Book Value and Company Financial Performance Through Economic Value Added Approach have a positive and significant influence to stock return of mining company that listed at Indonesia Stock Exchange in the period of 2008 2010.